What the Practitioner Knows Versus What the Client is Told: Neglected Dilemmas of Informed Consent in an Account of Single-System Experimental Designs - Wakefield, Jerome C.; Kirk, Stuart A. (Journal of social work education, 1997)
This article revisits the question, pursued in an interchange between Thomas (1978) and Gambrill and Barth (1980), on whether conflicts exist between service goals and research goals in the use of single-system experimental designs (SSDs) for practice evaluation. The authors approach the issue through an analysis of how informed consent is handled in one widely used textbook promoting the SSD model of practice evaluation. They argue that the text's suggestions for what to tell the client about reasons for using SSDs ignore knowledge acquisition goals emphasized elsewhere in the text, thus obscuring possible conflicts between the needs of the client and the requirements of SSD methodology. These failures of informed consent reveal largely neglected conflicts between practice and evaluation goals within the SSD model commonly taught to social work students.